2017
DOI: 10.1371/journal.pone.0183270
|View full text |Cite
|
Sign up to set email alerts
|

Deaths during tuberculosis treatment among paediatric patients in a large tertiary hospital in Nigeria

Abstract: BackgroundDespite availability of effective cure, tuberculosis (TB) remains a leading cause of death in children. In many high-burden countries, childhood TB is underdiagnosed and underreported, and care is often accessed too late, resulting in adverse treatment outcomes. In this study, we examined the time to death and its associated factors among a cohort of children that commenced TB treatment in a large treatment centre in northern Nigeria.MethodsThis is a retrospective cohort study of children that starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 37 publications
2
30
2
Order By: Relevance
“…The mortality rate seen in this study was low, which is similar to 3.5% reported from Ethiopia [15] but higher than 1.1% reported from India [12,13]. It is however lower than 6.0% reported from Lagos [14] and 28.4% from Kano [20]. The reason for the differences could be due to difference in methodology (some studies were retrospective others prospective, sample size); timing of presentation; presence of complications and other associated medical problems.…”
Section: Discussionsupporting
confidence: 69%
“…The mortality rate seen in this study was low, which is similar to 3.5% reported from Ethiopia [15] but higher than 1.1% reported from India [12,13]. It is however lower than 6.0% reported from Lagos [14] and 28.4% from Kano [20]. The reason for the differences could be due to difference in methodology (some studies were retrospective others prospective, sample size); timing of presentation; presence of complications and other associated medical problems.…”
Section: Discussionsupporting
confidence: 69%
“…Over half of the articles (61.5%) used cohort study design [7,9,13,14,[25][26][27][28][29][30][31][32][33][34][35][36] whereas the rest 38.8% were retrospective cross-sectional studies [10,[37][38][39][40][41][42][43][44] (Table 1). A total of 306,351 study participants with a sample size ranging from 227 in Ethiopia [41] to 170,017 in South Africa [37]; for studies conducted in Ethiopia and South Africa respectively.…”
Section: Characteristics Of Study Setting and Contextmentioning
confidence: 99%
“…A total of 306,351 study participants with a sample size ranging from 227 in Ethiopia [41] to 170,017 in South Africa [37]; for studies conducted in Ethiopia and South Africa respectively. Most of the study populations were from regions that are currently listed under the WHO as high TB burden countries [7,9,10,13,14,[26][27][28][29][30]32,33,[36][37][38][39][40][41][42][43][44][45].…”
Section: Characteristics Of Study Setting and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that factors associated with survival in cases of TB are related to the presence of specific comorbidities, including HIV/AIDS and diabetes mellitus [3][4][5][6][7][8][9]; some clinical characteristics, such as drug resistance, default of treatment, extrapulmonary and mixed forms [3,6,10,11]; specific sociodemographic characteristics of patients (age, male gender, schooling, color or race, etc); and lifestyle, such as alcoholism and smoking [4,7,11,12]. In Brazil, few studies of survival analysis after TB treatment were identified in the literature [7,13].…”
Section: Introductionmentioning
confidence: 99%